Tolerant From Below: Grassroots Movement and Interfaith Collaboration for Religious Moderation in Indonesia - Khoiruddin Zuhri, Mishbah; Dimas Maulana, Moch.; Mufti, Muhammad; Megah Safitri, Ririh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article explores the pivotal role of grassroots initiatives, focusing on Persaudaraan Lintas Agama - Interfaith Brotherhood-(abbreviated as Pelita) efforts to foster tolerance and combat intolerance in a multicultural society. It analyzes how Pelita mobilizes local support, addresses community-specific challenges, and promotes cultural change by embracing diversity. The research underscores grassroots movements' active role in advocating for community interests, ensuring policies align with local needs, and building solidarity against intolerant pressures. Key strategies, including interfaith education and tolerance campaigns, are highlighted. The article delves into Pelita's core values—brotherhood, volunteerism, and equality—illustrating how they shape programs and organizational structure. Initiatives like the Inter-Ummah Forum and peace camp are discussed for their strategic contributions to tolerance and interfaith dialogue. The article emphasizes Pelita's advocacy and support for marginalized groups, showcasing a comprehensive strategy that exemplifies how civil movements can significantly enhance communal tolerance and social harmony.